The Impact Of Work Stress, Financial Compensation and Non-Financial Compensation on Employee Employment at A Contruction Company In Pekanbaru - Sosiady, Mulia (MUI Kota Pekanbaru, 2023)
This research was done at the Construction Company in Pekanbaru. The aim of this study is to find out the impact of work stress, financial compensation and non-financial compensation on employee job satisfaction at the Construction Company in Pekanbaru. The sample in this study is an employee of the Construction Company in Pekanbaru of 35 people using saturated sampling or census techniques. To analyze the data in this study use quantitative descriptive techniques using double linear regression. Research findings show that work stress, financial compensation and non-financial compensation have a partial impact on employee job satisfaction. At the same time or simultaneously, work stress, financial compensation and non-financial compensation have a significant impact on employee employment satisfaction at the New Construction Company with known F counts of (35,566) ≥ Ftable (2,91) with a significant 0,000 ≤ 0,05, and a determination coefficient (R Square) value of 0,775 equals 77,5% which means that the work stress variables, economic compensation, and nonfinancy compensation affect employee job satisfaction of 77,5%.